2014
DOI: 10.3109/08820139.2013.833623
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of the Association between p53 Codon 72 Polymorphism and Susceptibility to Endometriosis

Abstract: This meta-analysis demonstrates that the p53 codon 72 polymorphism may be associated with susceptibility to endometriosis in East Asians, but not in Europeans and Latin Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…Although two meta-analyses addressing the association between the TP53 codon 72 polymorphism and endometriosis risk have been published, this study's findings indicate that the TP53 codon 72 polymorphism is associated with endometriosis risk, especially in Asian and Latin American populations, which is in part in contrast to both Jia's and Song's results (Jia et al, 2012;Song and Lee, 2014). Compared with the previous studies, this current meta-analysis has several particular strengths.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Although two meta-analyses addressing the association between the TP53 codon 72 polymorphism and endometriosis risk have been published, this study's findings indicate that the TP53 codon 72 polymorphism is associated with endometriosis risk, especially in Asian and Latin American populations, which is in part in contrast to both Jia's and Song's results (Jia et al, 2012;Song and Lee, 2014). Compared with the previous studies, this current meta-analysis has several particular strengths.…”
Section: Discussioncontrasting
confidence: 64%
“…This polymorphism (rs1042522) shows a single nucleotide substitution of G to C, resulting in the shift of arginine to proline in the amino acidic sequence. Previously, two research groups conducted metaanalyses concerning this theme and presented the same conclusion that TP53 codon 72 polymorphism was associated with the endometriosis risk in Asian populations rather than overall and in Caucasian populations (Jia et al, 2012;Song and Lee, 2014). By including certain new cohorts (Camargo-Kosugi et al, 2014;Chan, 2013;Frare et al, 2013;Huang et al, 2013;Kang et al, 2004;Silva, 2012) and applying different approaches for subgroup analyses, this study conducted an updated meta-analysis in order to further clarify the association between TP53 codon 72 polymorphism and susceptibility of endometriosis.…”
Section: Introductionmentioning
confidence: 92%
“…This polymorphism was associated with endometriosis only in East Asian women but not in European and Latin American women. 36 These issues may explain why we did not detect expression of p53 in our samples. Similarly, Uzan et al 37 reported weak positivity for c-erB-2 in the stromal tissue of endometriotic samples and found no evidence of gene amplification.…”
Section: Discussionmentioning
confidence: 78%
“…This polymorphism was associated with endometriosis only in East Asian women but not in European and Latin American women. 36 These issues may explain why we did not detect expression of p53 in our samples.…”
Section: Discussionmentioning
confidence: 78%
“…Second, six of the identified case-control studies for ER- α XbaI polymorphism included controls that were not consistent with the HWE. Deviation from the HWE in controls suggests certain biases during control selection and/or genotyping errors [ 45 ]. Third, the subjects in this meta-analysis were mostly of Chinese Han descent and only one study focused on the Chinese Hui population; hence, our results are only applicable to these ethnic populations because the number and type of genes influencing certain disease may not be identical in diverse populations.…”
Section: Discussionmentioning
confidence: 99%